Implementation Of Independent Curriculum In The Course Of Aqidah And Morals In Grade Iv (Evaluation Study Of Min 13 Pidie Jaya) - Syetti Aminah; Dhiauddin Dhiauddin; Saifuddin Saifuddin (Ludi Litterarri, 2025)
The Independent Learning Curriculum is an innovation in the world of education that gives students autonomy to determine their own learning path. In the context of this curriculum, students have the freedom to choose subjects, learning methods, and learning environments that can encourage creativity and innovation. This study aims to investigate teachers' understanding, implementation, and challenges and solutions faced in implementing the Independent Curriculum at MIN 13 Pidie Jaya, especially in the subject of aqidah akhlak in grade IV. The method used in this study is qualitative, with data collection techniques through observation, interviews, and document analysis. The research findings show that teachers' understanding of the Merdeka Belajar Curriculum is at a good level and continues to develop, although there is still a need for ongoing training. The implementation of the curriculum at MIN 13 Pidie Jaya shows significant progress, with the application of innovative learning methods and the use of technology that supports student interaction and understanding. In addition, this study also identified various challenges in implementation, including infrastructure and teacher competency issues. However, a commitment to continuous improvement and training is expected to overcome these obstacles, so that the learning process, especially in aqidah and akhlak, can take place effectively and in accordance with student needs.